Inulin and Lycium barbarum polysaccharides mitigate the diabetic inflammatory response by modulating bile acid metabolism to enhance regulatory T cell (Treg) activation in a rat model of diabetes - Lu, Haixia; Luo, Hongyan; Li, Peiling; Yang, Yan; Cao, Shilu; Zhang, Yanfang; Ma, Hongxia; Zhao, Qian; Zheng, Yali; Wang, Hao (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a chronic metabolic disease that poses a serious threat to health. Currently, there are no completely effective treatment options. Modulating intestinal flora and its metabolites may represent a promising new approach for diabetes therapy. Regulating intestinal microbiota and its metabolites through prebiotics, mediated by regulatory T (Treg) cells, could offer a novel strategy to improve the chronic inflammatory state associated with diabetes.ObjectiveThis study aimed to investigate the improvement of diabetes-related chronic inflammation by examining the effects of inulin (INU) and Lycium barbarum polysaccharides (LBP) in diabetic rats. This was achieved by modulating the bile acid metabolites of the intestinal flora through the FXR–FGF15–FGFR4 axis, thereby activating Treg cells in vivo and alleviating the inflammatory state associated with diabetes.MethodsA diabetic rat model was established using a high-fat diet and streptozotocin (STZ) injection. Sprague–Dawley rats were randomly allocated into four groups: type 2 diabetes mellitus (T2DM), T2DM with INU group (T2DM + INU), T2DM with LBP group (T2DM + LBP), and T2DM with INU and LBP group (T2DM + INU + LBP). After 8 weeks of intervention, the rats were euthanized, and relevant pathophysiological and biochemical indicators were analyzed.ResultsINU and LBP treatments significantly decreased the levels of inflammatory cytokines, including MCP-1, IL-18, NF-κB, NLRP3, superoxide dismutase (SOD), and malondialdehyde (MDA). Moreover, these alleviations of the inflammatory state of diabetes were partially attributed to the increased proportion of Treg cells. We found that the abundance of tauro β-muricholic acid (TβMCA) was reduced following INU and LBP treatment, whereas the relative abundances of chenodeoxycholic acid (CDCA), lithocholic acid (LCA), and hyocholic acid (HCA) were all increased compared to those in the untreated group. Mechanically, INU and LBP significantly influenced the negative feedback regulation of the FXR–FGF15–FGFR4 axis via intestinal bile acids, thereby increasing the proportion of Treg cells in the periphery of diabetic rats. Intriguingly, an increase in Treg cells after INU and LBP intervention was notably correlated with the improvement in the inflammatory state of diabetes.ConclusionsINU and LBP modulate bile acids derived from intestinal flora to improve the chronic inflammatory status of diabetic rats. Specifically, both exert their effectiveness by regulating gut microbial bile acid metabolites through the FXR–FGF15–FGFR4 axis to activate Treg cells. These findings provide an experimental basis for further exploration of the mechanism underlying the effects of this combination in diabetic animal models, which may contribute to clinical therapeutic practice for the control of the disease.